Pemanfaatan Bioarang pada Beragam Cekaman Air untuk Ketersediaan Fosforus Guna Meningkatkan Produktivitas Kedelai Anjasmoro (Glycine max L. Merrill.) - Angga Prasetya; Sri Nuryani Hidayah Utami; Fathi Alfinur Rizqi; Yulita Windi Nuraini; Melly Pradani (Institut Pertanian Bogor, 2024)
From 2021 to 2023, national soybean production has generally decreased due to shrinking cultivation areas. This study aimed to evaluate soybean productivity by applying biochar and regulating water volume. The experiment was conducted in the greenhouse of the Kuningan Soil Laboratory in April–November 2022 using a two-factor Complete Group Randomized Design; the first factor was the biochar dose (0, 10, 15, and 20 tons/ha), and the second factor was the water volume (50% (600 mL), 100% (1200 mL), and 125% (1800 mL). The physical parameters observed were moisture content and texture. The chemical parameters observed include pH, C-organic, cation exchange capacity (CEC), base cations (Ca, Mg, K, Na), N-total, P-total, and P-available. The data were analyzed using analysis of variance followed by Duncan's Multiple Range Test to compare between treatments. The results showed that applying biochar with a dose of 20 tons/ha and 100% water volume can significantly improve soil chemical properties. pH, CEC, Ca-available, Mg-available, K-available, N-available, P-total, P-available, and N-total are markedly affected by the correct biochar dose and water volume. The more applications of biochar, the better the chemical properties of the soil. The provision of water according to needs will increase the availability of nutrients for plants. Keywords: biochar, phosphorous, irrigation, soybean